DAGUSIBU education and Beyond Use Date Medicine in the Community at the Rejosari Pekanbaru Community Health Center - Agustini, Tiara Tri; Rahmat, Rosita Dewi; Tantrica, Monica Dora; Astari, Natasya; Fajriah, Nurul; Permata Sari, Poppy Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Medicines are substances or combinations of substances, including biological products, which are used to influence or study physiological systems or pathological conditions in connection with the diagnosis, prevention, healing, recovery, improvement and prevention of health in humans. Medicines that can be used are medicines that meet certain quality standards. One of the parameters that influence the quality of medicines is the storage conditions of the medicine, the expiration date when the primary packaging is intact and the Beyond Use Date (BUD) or the deadline for using the medicine after it has been formulated or prepared or after the primary packaging is opened or damaged. The activity was carried out on April 3 2024 at the Rejosari Community Health Center, Pekanbaru city, Riau Province. The targets for this activity are people who come to the Rejosari Community Health Center, Pekanbaru City, Riau Province, totaling 25-30 people. Activities were carried out face to face using media in the form of educational leaflets about Beyond Use Date and DAGUSIBU at the Rejosari Community Health Center. This outreach activity was carried out by PKPA STIFAR Riau students which resulted in patient enthusiasm for following the rules that have been explained regarding Beyond use date and DAGUSIBU so that they do not use medicines carelessly and know what to do with medicines according to their needs.